ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Konsumen Waroeng Steak & Shake Cabang Jl. Sriwijaya 11 Semarang) - Kurniasari, Nova Dhita; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2013)
Research aims to know whether price, quality of product, and service quality influence the decision purchase consumers Waroeng Steak & Shake and analyzing factor the most dominant ineffecting decision purchase consumers Waroeng Steak & Shake in Semarang.The population in this research is the consumer of consumers Waroeng Steak & Shake. The sample is taken from 100 respondents with the Non-Probability Sampling technique withAccidental Sampling approach that the determination of the sample is accidentally taken—those who meet the researcher can be a sample if deemed appropriate.The result showed price, quality of product, and service quality have positive and significant impact to the purchasing decision. Based on the statistic data analysis, the indicators in this research is valid and the variable is reliable. In the classical testing assumption, the regressionmodel is free multicollonierity, the heteroscedasticity does not occur, and normal distribution. Order individually from each of the most influential variable is the variable quality of product andservice quality, while the most influential variables are low is the price. The suggestion from the writer to increase the consumer's purchasing decision can be carried out by means of competitivepricing, increasing the diversity of products, and improve the quality of his service. Waroeng Steak& Shake the need to preserve the elements which have been rated good (price, quality of product, and service quality) by the customer as well as the need to fix the things that are lacking (promotion).